2003
DOI: 10.1007/s00018-003-3207-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane and nuclear melatonin receptor mRNA and protein in the mouse immune system

Abstract: The neurohormone melatonin plays a fundamental role in neuroimmunomodulation of several mammalian species, including mice. This effect is supported by the existence of specific melatonin-binding sites in murine immunocompetent organs. Moreover, using melatonin receptor analogues, several effects of the neurohormone on mice physiology through its membrane and nuclear receptors have been described. The expression of these receptors has never been studied, despite indirect evidence showing the presence of melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 54 publications
6
82
0
5
Order By: Relevance
“…These data are in accordance with reports of CarrilloVico et al [22,29] , who suggested that IL-2 secretion by lymphocytes could be the marker of an autocrine action of melatonin. The function of MT1R and MT2R in target tissues was derived primarily from pharmacological studies using 2 prototype melatonin receptor antagonists, luzindole and 4P-PDOT [14,30] ; hence, we used a similar approach for the present study.…”
Section: Discussionsupporting
confidence: 82%
“…These data are in accordance with reports of CarrilloVico et al [22,29] , who suggested that IL-2 secretion by lymphocytes could be the marker of an autocrine action of melatonin. The function of MT1R and MT2R in target tissues was derived primarily from pharmacological studies using 2 prototype melatonin receptor antagonists, luzindole and 4P-PDOT [14,30] ; hence, we used a similar approach for the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The RT-PCR primers conditions for common RORα fragment and RORα1-4 isoforms were as described (common fragment, ref. 47 ; isoforms, ref. 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of receptors in the human immune system was first shown by the demonstration of 2-[ 125 I]iodomelatonin binding sites in peripheral blood mononuclear cells (PBMCs) (LopezGonzalez et al, 1993). Membrane-bound melatonin receptors have since been characterized in thymus and spleen of many species (Carrillo-Vico et al, 2003b) as well as in peritoneal macrophages (Garcia-Perganeda et al, 1999). In mammals, membrane-bound melatonin receptors are distinguished pharmacologically as subtypes MT 1 and MT 2 , and are members of the G-protein-coupled receptor superfamily (Dubocovich, 1995).…”
mentioning
confidence: 99%